STUDIES ON STEWART PLATFORM – A REVIEW - Alina-Elena LUPULESCU (MACHIDON) (Fiabilitate şi Durabilitate, 2023)
The Stewart Platform is a type of parallel manipulator with six Degrees of Freedom (DOF). The full assembly is a parallel robotic system consisting of a rigid body top or mobile plate connected through six prismatic actuators to an immobile base plate. The actuators (legs) also have an in-built mechanism that allows changing their lengths individually (Fig.1).